2018
DOI: 10.1186/s41199-018-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular extension is not a significant prognostic indicator in non-squamous cancers of the major salivary glands

Abstract: Background Extracapsular extension (ECE) is a well-established prognostic feature in squamous cell cancers of the head and neck. Although some extrapolate data from mucosal head and neck cancer to include ECE as a high-risk feature in salivary gland cancers, data is lacking about ECE’s prognostic value for these malignancies. We investigate whether ECE is a significant prognostic indicator in pathologic node-positive cancers of the major salivary glands. Methods A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…13,14 However, other studies have suggested that ENE lacks significant prognostic value for certain histological subtypes, such as non-SCC tumors of the major salivary glands. 15…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 However, other studies have suggested that ENE lacks significant prognostic value for certain histological subtypes, such as non-SCC tumors of the major salivary glands. 15…”
mentioning
confidence: 99%
“…More recently, ENE has been suggested to be a potential predictor of poorer survival in human papillomavirus (HPV)–positive oropharyngeal SCC 13 , 14 . However, other studies have suggested that ENE lacks significant prognostic value for certain histological subtypes, such as non‐SCC tumors of the major salivary glands 15 …”
mentioning
confidence: 99%
See 1 more Smart Citation